A estética da verossimilhança no romance Julia ou A Nova Heloísa de Jean-Jacques Rousseau - BORRALHO, César Henrique de Paula (2015)
The research presented intends understand philosophical and literary aspects of Rousseau's aesthetics that establishi identify from the likelihood of nature and culture. For this purpose we analyze the Rousseau's critic to the place of reason imposed by the Enlightenment of the eighteenth century and the new meaning of this in his epistolary novel Julie or the New Heoise, granting primacy to feeling and makes it a key element in its condensed philosophy in the romance experienced by the love between Santi-Preux and Julia, central characters. To address the mentioned problem, it objectives to analyze the reason for exaltation in the Enlightenment of the eighteenth century as human progress proposal and inconsistencies this reason given by Rousseau as a promoter of corruption and social degeneration. We investigate , therefore, how it holds the right focus shift to the feeling recommended by Rousseau in order to make good use of these two human faculties in an attenpt to restore good manners. In this sense, we intend to understand the call likelihood, the Rousseau transparency that is mirrored by the simple family life Julia in Clarens, directing our analysis to the limits of representation that aim in false mirrors of reality and hinders the inner feelings marked by expression of a sensitive heart undeserved by reason.